2005
DOI: 10.1002/art.21031
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the interferon‐α pathway identifies a subgroup of systemic lupus erythematosus patients with distinct serologic features and active disease

Abstract: Objective. Gene-expression studies have demonstrated increased expression of interferon (IFN)-inducible genes (IFIGs) in peripheral blood mononuclear cells (PBMCs) of many patients with systemic lupus erythematosus (SLE), with a predominant effect of type I IFN. This study examined the hypothesis that increased disease severity and activity, as well as distinct autoantibody specificities, characterize SLE patients with activation of the type I IFN pathway.Methods. Freshly isolated PBMCs from 77 SLE patients, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

44
544
8
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 622 publications
(611 citation statements)
references
References 47 publications
44
544
8
3
Order By: Relevance
“…Plasmacytoid DCs can be induced to produce large amounts of type I interferons by TLR-9 agonists in conjunction with autoantibodies (30), and "classic" severe SLE, in which anti-RNP and anti-dsDNA responses occur, has been associated with a type I interferon-induced gene signature (13). These plasmacytoid DCs express TLR-7 and TLR-8, the human homologs to murine TLR-7 (23), in the same cellular compartment (and connected to the same downstream second signaling apparatus) as TLR-9 (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmacytoid DCs can be induced to produce large amounts of type I interferons by TLR-9 agonists in conjunction with autoantibodies (30), and "classic" severe SLE, in which anti-RNP and anti-dsDNA responses occur, has been associated with a type I interferon-induced gene signature (13). These plasmacytoid DCs express TLR-7 and TLR-8, the human homologs to murine TLR-7 (23), in the same cellular compartment (and connected to the same downstream second signaling apparatus) as TLR-9 (31).…”
Section: Discussionmentioning
confidence: 99%
“…In a small series of mice, we have previously found that direct immunization of a susceptible animal with RNP antigen could induce MCTD-like serologic responses and clinical manifestations (12). However, reactivity to RNP components has recently been shown to correlate with the development of severe disease in lupus, including the development of GN (13). Reconciling the role of RNP antigens both in MCTD, a relatively mild lupus-like disorder that does not target the kidneys, and in severe kidney-targeted SLE has been difficult.…”
mentioning
confidence: 99%
“…All SLE patients had active disease, and their mean score on the SLE Disease Activity Index (SLEDAI) (32) was 17 (range [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. SLE patients had a mean C-reactive protein (CRP) level of 5.7 mg/liter, and a mean erythrocyte sedimentation rate (ESR) of 40 mm/hour.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Most strikingly, gene expression profile analyses have shown that peripheral blood mononuclear cells from SLE patients harbor a signature resembling that of cells exposed to IFNab, and that this signature can distinguish SLE patients from patients with rheumatoid arthritis. 3,5 New Zealand hybrid mice are a well-studied mouse model of lupus-like disease. In these animals, the female F1 offspring of New Zealand black (NZB) crossed with New Zealand white (NZW) mice develops high levels of circulating autoantibodies against nuclear antigens such as DNA and histones, immune complex (IC) formation and deposition in the kidneys, and ultimately kidney failure due to damaged glomeruli.…”
Section: Introductionmentioning
confidence: 99%